(untitled) (Economic and Political Thought, 2019)
The political scene of the Federal Republic of Germany was traditionally recognised as extraordinarily stable. However, in the second decade of the 21st century the pace of changes in it has clearly quickened and they are reshaping it in the long term. The changes are conditioned by internal policy as well as global trends. In the author’s opinion, the change in the German political scene does not take place rapidly but one can see the weakening of the left wing, the change of the party playing the role of a pivotal one, and probably the movement of Christian democracy towards the right wing under the pressure of radical tendencies. The growing difference between the socalled old and new federal states constitutes the biggest threat because the latter prove to be much more vulnerable to the influence of radically right movements.